2010
DOI: 10.3109/13668251003717928
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and intellectual disability in New Zealand

Abstract: There were more obese men and women with ID in this sample than would be expected, and women in Classes II and III are of particular concern. Research into the factors and potential interventions specific to men and women in this population to promote and maintain weight loss are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 7 publications
4
35
0
1
Order By: Relevance
“…• Obesity in men with intellectual disability significantly less vs. women with intellectual disability Stedman and Leland (2010) • Women with intellectual disability ~2 times (p < .001)& men ~ 1 ½ times(p < .05) likely to be obese vs. women & men, resp. in the general population.…”
Section: Mikulovic Et Al (2014)mentioning
confidence: 99%
See 2 more Smart Citations
“…• Obesity in men with intellectual disability significantly less vs. women with intellectual disability Stedman and Leland (2010) • Women with intellectual disability ~2 times (p < .001)& men ~ 1 ½ times(p < .05) likely to be obese vs. women & men, resp. in the general population.…”
Section: Mikulovic Et Al (2014)mentioning
confidence: 99%
“…Researchers across the world have reported the prevalence of being overweight and obese among adults with intellectual disability to be 28% -71% and 17% -43%, respectively (Barnes, & Echteld, 2012& Echteld, , 2009Emerson, Hatton, Baines, & Robertson, 2016;Haider, Ansari, Vaughan, Matters, & Emerson, 2013;Hsieh, Rimmer, & Heller, 2014;Koritsas & Lacono, 2016;Martínez-Leal et al, 2011;Melville et al, 2008;Mikulovic et al, 2014;Sohler, Lubetkin, Levy, Soghomonian, & Rimmerman, 2009;Stedman & Leland, 2010;Temple, Foley, & Lloyd, 2014;Wallace & Schluter, 2008; Table 1). The evidence is mixed on whether the prevalence of being overweight and/or obese is similar or proportionally higher or lower for individuals with intellectual disability versus the general population.…”
Section: Prevalence Of Being Overweight and Obesementioning
confidence: 99%
See 1 more Smart Citation
“…Duplicates removed (n = 868) 4 articles reported on same study 2 articles reported on same study 108,115,116,132,138,141 ) and South Africa (n = 2 131,134 ). Primarily, the included studies were cross-sectional observational (n = 31 81,82,98,[100][101][102]104,106,[109][110][111]114,116,119,121,124,[126][127][128][129][130][131][132][133][134][135]137,139,142,143,145 ).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Compared to the general population, people with intellectual disability have higher overall levels of chronic disease, such as diabetes (18.5%) and greater use of primary care (Carey et al, 2016). Obesity and respiratory disease are significant comorbidities, with obesity affecting up to 51% of people with intellectual disability compared to 29% of the general population (Stedman & Leland, 2010) and respiratory disease affecting 19.8% compared with 15.5%. The main cause of death is respiratory disease (52%) related to pneumonia and aspiration.…”
Section: Health Outcomesmentioning
confidence: 99%